The Microbes Planet - Shakeeb Arsalaan Bajunid, Siti Farhana Bajunid; Zulkifli, Mohd Amirul Faiz; Md. Zuri, Izyan Fartini; Kueh, Harisson; Saad, Wan Zuhainis (UTM Academic Leadership (UTMLead), Universiti Teknologi Malaysia, 2016)
The Microbes Planet is a website full of interactive information specially designed from Malaysian primary and secondary schools for Science and Biology subjects. Together with a YouTube channel called MicrobeBuzz, provide information and interactive activities to enhance learning of Science and Biology among school students. A fun way of learning.